Anorectal malformation with a rectovestibular fistula in a 14-year-old adolescent. Case report - Dueñas-Ramírez, Juan Carlos (2023)
Anorectal malformation (ARM), commonly mislabeled as "imperforate anus," stands out as one of the most prevalent congenital anomalies. The ARM classification encompasses all congenital caudal anomalies associated with an imperforate anus. While the majority of cases are identified during the neonatal period or early childhood, there are instances where diagnosis occurs in adolescence. This manuscript aims to present the case of a 14-year-old patient with an anorectal malformation featuring a late-diagnosed rectovestibular fistula. The corrective procedure employed was a posterior sagittal anorectoplasty, yielding a positive postoperative outcome. The case analysis includes a clinical history description, patient images, a surgical technique description, and a literature review on anorectal malformations. In conclusion, anorectal malformation proves to be a common congenital anomaly, with sporadic cases being diagnosed in adolescence. In our developing country, various factors contribute to delayed diagnoses, such as misinformation, illiteracy, and poverty. To mitigate complications, achieve favorable postoperative results, and enhance the quality of life for these patients, early identification of ARM cases is crucial. Therefore, it is imperative to educate medical professionals and raise awareness among family members to encourage early consultations.